Self reported practice of e-waste disposal and awareness about its health hazards among people at various levels in selected urban slums of Bangalore: a cross sectional study - Duraisamy, Shanmugapriya; Narayanappa, Ramakrishna Reddy; Sobagiah, Ranganath Timmanahalli (International Journal Of Community Medicine And Public Health, 2017)
Background: With advent of advancement in technologies and change in people’s life style, the amount of E-waste (electronic waste) generated is increasing drastically every year, Mismanagement of these E-waste leads to diminishing natural resources, causing irreparable damage to the environment and health of the people. When it comes to the reduction, the onus is on both the consumer and the producer. Proper awareness on the health hazards and disposal practice of E waste plays a crucial role in curbing this problem. The objectives of the study were to assess the E-waste segregation and disposal practice at various levels and to assess the knowledge about Proper disposal and health hazards of E-waste. Methods: A community based crossed sectional study was conducted among 120 randomly selected individuals (distribution, consumer and waste collection level) for a period of three months in the urban field practice area of Bangalore Medical College & Research Institute. Data regarding their knowledge and practice on E-waste disposal and its hazards has been collected using semi structured questionnaire and analysed using SPSS 23.0. Results: Knowledge about disposal was found to be 20%, 15% and 5% respectively at distribution, consumer and waste collector levels. Only around 6% had practiced proper waste segregation. Knowledge pertaining to health hazards were found to be negligible. Conclusions: With the increased burden the knowledge and practice were found to be highly inadequate. And it is a high time to intervene at the earliest by creating proper awareness and providing the requisite for proper disposal of E waste.